STUDENTS’ SILENCE IN DIFFERENT EFL LEARNING PROCESSES AND THE PROLONGED EFFECTS: AN AUTOETHNOGRAPHY STUDY - Nita Listiyaningtyas; Akmal Akmal (IKIP Siliwangi, 2023)
Students’ silence rapidly grows during online learning and continually affects the present learning process. Students showed various reasons for being silent. The study aims to determine students’ reasons for being silent in different EFL learning processes; online learning, limited face-to-face learning, and a whole class of face-to-face learning, and its prolonged effect on their learning behavior. The study used qualitative research with an autoethnography method. The study’s data was collected through observation, narrative journaling, and a semi-structured interview. The semi-structured interview was conducted with five sample students from five different classes, chosen purposively based on the researcher’s criteria. The finding shows that students are silent in online learning because the English learning process is not fun, they are afraid of making mistakes, and they cannot interact with the teacher and other friends. Students’ silence decreases when they have a limited class of face-to-face learning and almost entirely disappears during the whole class of face-to-face learning. However, students’ silence continued until the present EFL class, affecting their cognitive and social skills. Teachers need to apply appropriate teaching strategies to break students’ silence and improve their participation in the learning process.